Expression and function analysis of two naturally truncated MyD88 variants in the Pacific oyster Crassostrea gigas. Issue 2 (August 2015) - Xu, Fengjiao; Zhang, Yang; Li, Jun; Zhang, Yuehuan; Xiang, Zhiming; Yu, Ziniu
Abstract: Myeloid differentiation factor 88 (MyD88) is the classic signaling adaptor that mediates Toll/interleukin-1 receptor (TIR/IL-1R) dependent activation of nuclear factor-kappa B (NF-κB). In this study, two naturally truncated MyD88 members were identified from the Pacific oyster ( Crassostrea gigas ), namely CgMyD88-T1 and CgMyD88-T2. The full-length cDNA of CgMyD88-T1, CgMyD88-T2 are 976 bp and 1038 bp in length, containing an ORF of 552 bp and 555 bp, respectively. The two ORF encode a putative protein of 183 and 184 amino acids, respectively, with a calculated molecular weight of about 21 and 22 kDa. When compared to complete MyD88 paralogues, we found that both CgMyD88-T1 and CgMyD88-T2 contain only TIR domain but lack DD (Death Domain), which share 90.8% of similarity and 71.7% of identity with each other. Phylogenetic tree demonstrated that CgMyD88-T1 and CgMyD88-T2 clustered together and belonged to mollusk branch. Meanwhile, genomic arrangement analysis displayed that the two truncated MyD88s were distributed in tandem in one scaffold, revealing that they may originate from one truncated MyD88 ancestor recently. Expression profile showed that both of CgMyD88 variants were ubiquitously expressed in all tested tissues with highest expression in the gills and hemocytes, respectively. Both truncated CgMyD88 mRNAs were significantly up-regulated in hemocytes under HKLM (heat-killed Listeria monocytogenes ) and HKVA (heat-killed Vibrio alginolyticus ) challenge. Moreover, either CgMyD88-T1 or CgMyD88-T2 were able to inhibit MyD88 activated Rel/NF-κB activity in HEK293 cell, demonstrating their negative role in regulating MyD88-mediated immune signaling. Highlights: First experimental evidence for presence of Truncated Myd88 variants in mollusks. Two truncated Myd88 variants were distributed in tandem in one scaffold. Truncated Myd88 variants could be significantly up-regulated by immune challenge. Truncated Myd88 variants could inhibit Rel/NF-κB activity in HEK293 cell.